Error-proofing your research common mistakes and how to address them - Trinidad, Jose Eos (Ateneo de Manila University Press, 2019)
Students and beginning researchers often find writing research difficult, and the process itself may be filled with mistakes and missteps. To help address or avoid some of these mistakes, Error-Proofing Your Research outlines common research mistakes, from the start of the research project until its submission for potential publication. The book illustrates these mistakes and suggests ways to avoid or amend them.